Bilateral Unstable Severe Valgus Slipped Capital Femoral Epiphysis: A Case Report. Issue 1 (January 2022) - Venkatadass, K.; Durga Prasad, V.; Jain, Deepak; Rajasekaran, S.
Abstract : Case: Bilateral valgus slipped capital femoral epiphysis (SCFE) is a rare condition with few cases reported in the literature. However, there are no reports of bilateral unstable valgus SCFE. We report a unique case of bilateral acute-on-chronic unstable valgus SCFE with severe coxa valga in a 9-year-old girl. She was treated with bilateral capital realignment procedure along with subtrochanteric osteotomy and had a good clinical outcome. Conclusion: We hitherto report a rare case of bilateral unstable valgus SCFE which was successfully managed. This report also highlights the importance of the need for additional osteotomies to address the deformity.